A change in the bacterial community of spider mites decreases fecundity on multiple host plants. Issue 6 (11th October 2018) - Zhu, Yu‐Xi; Song, Yue‐Ling; Hoffmann, Ary A.; Jin, Peng‐Yu; Huo, Shi‐Mei; Hong, Xiao‐Yue
Abstract: Bacterial symbionts may influence the fitness of their herbivore hosts, but such effects have been poorly studied across most invertebrate groups. The spider mite, Tetranychus truncatus, is a polyphagous agricultural pest harboring various bacterial symbionts whose function is largely unknown. Here, by using a high‐throughput 16S rRNA amplicon sequencing approach, we characterized the bacterial diversity and community composition of spider mites fed on five host plants after communities were modified following tetracycline exposure. We demonstrated that spider mite bacterial diversity and community composition were significantly affected by host plants and antibiotics. In particular, the abundance of the maternally inherited endosymbionts Wolbachia and Spiroplasma significantly differed among spider mites that were reared on different plant species and were completely removed by antibiotics. There was an overall tendency for daily fecundity to be lower in the mites with reduced bacterial diversity following the antibiotic treatment. Our data suggest that host plants and antibiotics can shape spider mite bacterial communities and that bacterial symbionts improve mite performance. Abstract : The bacterial diversity tended to decrease after antibiotic exposure but was also influenced by host plant type. The abundance of the maternally inherited endosymbionts Wolbachia and Spiroplasma was reduced following antibiotic exposure although the extent of reduction differed among host plants.